LITERARY INTERPRETATION OF SOCIAL PSYCHOLOGY IN THE NOVEL “MARTIN EDEN” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Literary interpretation of social psychology in the novel “Martin Eden” is analyzed in the article.